Merawat Perjuangan: Politik Kesabaran Perempuan dalam Menuntut Keadilan Lingkungan di Cilacap - Miftahul Huda (Jurnal HAM, 2024)
The PT S2P coal-fired power plant (CFPP) in Cilacap has generated considerable profits for the capitalist country since 2006, while simultaneously causing environmental damage and rendering local communities vulnerable. This paper employs a case study approach to examine the role of women's agency from the Global South in the social movement for environmental justice. It considers how global-local economic and political relations in Cilacap influence this movement. It sought to explain women's agency in claiming the right to a healthy and decent environment by testing the theory of the politics of patience, which located women outside and against state and corporate power. Through ethnography, in-depth interviews, and meetings with activists, public officials, and NGOs, this study depicted women as political actors in the face of the negative impacts of the state-electricity company nexus. In their struggles, women were confronted with gender stereotypes that were shaped by the state and reinforced by society. These stereotypes prevented women from participating in social movements that demanded their rights. The most important finding was that the nurturing role of women has ensured that the struggle for the right to a healthy and decent environment has lasted longer and has remained outside of and against the state.